Dynamics of Political Polarization - Baldassarri, Delia; Bearman, Peter (American Sociological Review, 2007)
This article accounts for two puzzling paradoxes. The first paradox is the simultaneous absence and presence of attitude polarization—the fact that global attitude polarization is relatively rare, even though pundits describe it as common. The second paradox is the simultaneous presence and absence of social polarization—the fact that while individuals experience attitude homogeneity in their interpersonal networks, their networks are characterized by attitude heterogeneity. These paradoxes give rise to numerous scholarly arguments. By developing a formal model of interpersonal influence over attitudes in a context where individuals hold simultaneous positions on multiple issues, we show why these arguments are not mutually exclusive and how they meaningfully refer to the same social setting. The results from this model provide a single parsimonious account for both paradoxes. The framework we develop may be generalized to a wider array of problems, including classic problems in collective action.